Structural characterization and rheological properties of a gel-like β-d-glucan from Pholiota nameko. (1st August 2017) - Sovrani, Vanessa; de Jesus, Liana Inara; Simas-Tosin, Fernanda Fogagnoli; Smiderle, Fhernanda Ribeiro; Iacomini, Marcello
Highlights: β-d -Glucan fractions were isolated from fruiting bodies of Pholiota nameko . NMR and methylation analyses confirmed the presence of (1 → 3), (1 → 6)-β-D-glucan. Crude and purified β-D-glucan showed shear-thinning behavior. The tested fractions presented thermal stability in a wide temperature range. P. nameko glucans are promising thickener and gelling agents for food products. Abstract: A crude fraction (SCW) was extracted with cold water from Pholiota nameko and showed mannose (24.1%), galactose (44.9%) and glucose (31%). Purification procedures resulted in a polysaccharide fraction (bG-PN), that showed only glucose. NMR and methylation analyses of bG-PN indicated a β-d -glucan-(1 → 3)-linked, substituted at O-6 by β-d -Glc p or (1 → 6)-linked β-d -Glc p side chains. Rheological studies of crude and purified fractions at the same concentration showed similar shear-thinning behavior and gel-like structure which indicates no need to isolate the polymer to achieve some desirable rheological properties. SCW (at 1% and 2%) and bG-PN (at 2%) presented thermal stability during heating and cooling, suggesting that the physical structure of gels (SCW and bG-PN at 2%) and viscoelastic fluid (SCW at 1%) formed were not altered in the tested temperature range. Our results suggest that P. nameko β-d -glucans can be applied in different food preparations as thickener or gelling agents modifying their rheological properties.